Perancangan dan Implementasi Foto Profil Guru di Smp Charitas Batam - Jimmy Pratama; Jeffri Liu; Deli Deli (National Conference for Community Service Project (NaCosPro), 2025)
The unavailability of complete and professional teacher profile photo documentation has become a challenge for SMP Charitas Batam in fulfilling various school needs. To address this issue, a practical work project was carried out focusing on the creation of teacher profile photos using the Multimedia Development Life Cycle (MDLC) method, which includes the stages of concept, design, material collecting, assembly, testing, and distribution. The implementation process was conducted in stages, starting from photo sessions, photo editing using image editing software, to organizing the final files into a structured digital folder using Google Drive. The result of this activity was a collection of high-quality JPEG-format teacher profile photos that have been submitted to the school. This documentation not only supports administrative visual data needs but can also be utilized for publication purposes and the development of a school information system. This project demonstrates that a structured approach to digital documentation can enhance the professionalism of educational institutions and provide students with real-world experience in implementing multimedia-based projects.